2022
DOI: 10.1007/s00109-022-02270-8
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic HRC induces hepatocyte pyroptosis and HSCs activation via NLRP3/caspase-1 pathway

Abstract: The histidine-rich calcium-binding protein (HRC) is a regulator of Ca2 + homeostasis and it plays a signi cant role in liver brosis. Pyroptosis, a speci c in ammatory cell death, can lead to HSCs activation and liver brosis. However, the role of HRC in pyroptosis has not been explored. In this study, we demonstrated that HRC, mainly located in the hepatocyte, was overexpressed in brotic liver tissues. We further found that enforced expression of HRC in hepatocytes induced pyroptosis and HMGB1 release, and subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
(27 reference statements)
0
6
0
Order By: Relevance
“… 41 , 42 Furthermore, dying hepatocytes induced by pyroptosis can release HMGB1, which promotes HSC activation. 43 Suppression of hepatocyte pyroptosis is found to reduce liver fibrosis. 44 , 45 …”
Section: Pcd Participates In the Pathogenesis Of Liver Fibrosismentioning
confidence: 99%
“… 41 , 42 Furthermore, dying hepatocytes induced by pyroptosis can release HMGB1, which promotes HSC activation. 43 Suppression of hepatocyte pyroptosis is found to reduce liver fibrosis. 44 , 45 …”
Section: Pcd Participates In the Pathogenesis Of Liver Fibrosismentioning
confidence: 99%
“…Similarly, NLRP3 activation promotes HF. In humans with HF and CCL 4 ‐induced mouse models of HF, Wu et al (2022) found that the histidine‐rich calcium‐binding protein, a homeostatic regulator of Ca 2+ , activates NLRP3 inflammasomes and induces pyroptosis via the NLRP3/caspase‐1 pathway. The subsequent release of the DAMP molecule HMGB1 then promotes the activation of HSCs, which leads to or exacerbates extracellular matrix protein synthesis and deposition and subsequently promotes HF (Xie et al, 2022).…”
Section: Liver Diseases and Pyroptosismentioning
confidence: 99%
“…The subsequent release of the DAMP molecule HMGB1 then promotes the activation of HSCs, which leads to or exacerbates extracellular matrix protein synthesis and deposition and subsequently promotes HF (Xie et al, 2022). Moreover, the NLRP3 inhibitor MCC950 and the caspase‐1 inhibitor VX‐765 attenuate histidine‐rich calcium‐binding protein‐mediated pyroptosis and HSC activation, which in turn attenuate HF (Wu et al, 2022). Irisin inhibits reactive oxygen species (ROS) overexpression and NLRP3 inflammasome activation, thereby suppressing or improving the inflammatory response and reducing sepsis‐induced LI (Li, Tan, et al, 2021).…”
Section: Liver Diseases and Pyroptosismentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of NLRP3 inflammasome prompts ASC to recruit pro-caspase-1, leading to the auto-catalytic activation of caspase-1, and the cleaved caspase-1 cleaves GSDMD into the N-terminal domain of GSDMD (GSDMD-N) and forms pores on the plasma membrane to facilitate the maturation and release of IL-1β and IL-18, thereby causing pyroptosis [ 18 , 19 ]. Proir studies have demonstrated that supression of the NLRP3/Caspase-1 pathway can not only significantly inhibit the formation of fibrosis after acute kidney injury, but also induce hepatocyte pyroptosis to curb hepatocyte fibrosis [ 20 , 21 ], indicating that the NLRP3/caspase-1 axis-mediated pyroptosis is closely bound up with the process of cell fibrosis. Moreover, NaB impedes high glucose-induced NLRP3 overexpression in human monocyte macrophage THP-1 cells, negatively regulates NLRP3-mediated inflammatory signaling pathways, suppresses macrophage activation and secretion of pro-inflammatory mediators (such as IL-18 and IL-1β), reduces intestinal inflammation level, and limits colitis-associated cancer development [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%